MODEL DAN STRATEGI PEMBELAJARAN - Indriawati; Imam Buchori; Acip; Sekarmaji Sirrulhaq; Encep Solihutaufa (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
Efforts to improve the quality of learning require positive changes, to be able to manage learning effectively and efficiently an educator requires knowledge of learning models and strategies. Therefore, in learning reform, what should be done is how to change the pattern of learning activities that can create a learning atmosphere and the learning process feels more interesting. Quality learning strategies are one form of effort to change the pattern of learning models that have been used in the learning process. All activities of educators and students in realizing an effective learning process are formed in a combination of the stages of activities, methods, learning media and the time used in learning activities are summarized in the learning strategy. The purpose of this study was to determine the models and strategies in the learning process. This study uses a qualitative approach to the type of library research. The data sources of this research come from books, journals and scientific articles related to learning models and strategies. The results of the study show that the right learning strategy will foster students to be more creative and independent. The selection of appropriate learning models and strategies will be able to foster students to be able to think creatively, independently and adaptively to various situations that occur and may occur. Educators think about and prepare appropriate learning models and strategies so that students are able to receive and process information conveyed by educators.